Visual Art in Motion Comic Sirup Manis Sofia - Kris D Djayanti; Christian Aditya (ULTIMART Jurnal Komunikasi Visual, 2016)
Helping each other is one of moral values that are important to introduce to children because humans are social creatures. To convey this message, required a media that suite children to attract their interest, which is motion comic. To make motion comic become more attractive, the visual style that used is modernist cartoon style that popular in animation and illustrations of the 1950s. Keywords: helping, motion comic, modernist